Discourse of the Collective Subject and Content Analysis on qualitative aproach in Health (Research, Society and Development, 2021)
The qualitative approach is related to subjectivity, including the perspective of the subjects involved through direct and personal contact between the researcher and the social agents. Some qualitative research are characterized by analyzes of information that can not be measured, but that aim at the understanding of language and its meanings in its forms and contexts of expression. In this article aimed at researchers who are new to the qualitative approach, the objective was to present the Collective Subject Discourse and Content Analysis in an articulated way to the use of the interview as options for the development of research of this nature. From a theoretical and comparative analysis, it was verified that there are methods that approach the possibility of responding to the intentions of the research, but there is no universal model applicable to all cases and sufficient. The key is that researchers take ownership of existing methods and techniques and make a conscious choice of the path in which the analysis will be conducted.